How Did the Pandemic Become One of the Main Innovation Drivers of the Modern Economy? - Ishbulatova A.I.; Minullina Ch.G.; Nurgalieva R.R. (Uzbekistan Open Conference, 2025)
The report examines pre-COVID technology trends and the key changes brought about by the pandemic. It presents specific examples of successful business adaptation to the new conditions, analyzes the impact of the crisis on changes in consumer behavior, the growth of startups, and the expansion of venture investments, and highlights the positive consequences of the COVID-19 period.
Keywords: Pandemic; consumer behavior; digitalization; quarantine; economy; lockdown; online retail; digital currencies; remote banking services (RBS)